A 1.9 Earth radius rocky planet and the discovery of a non-transiting planet in the Kepler-20 system - Buchhave, Lars A.; Lundkvist, Mia S. (The astronomical journal, 2016)
Kepler-20 is a solar-type star (V = 12.5) hosting a compact system of five transiting planets, all packed within the orbital distance of Mercury in our own solar system. A transition from rocky to gaseous planets with a planetary transition radius of ∼1.6 has recently been proposed by several articles in the literature. Kepler-20b ( ∼ 1.9 ) has a size beyond this transition radius; however, previous mass measurements were not sufficiently precise to allow definite conclusions to be drawn regarding its composition. We present new mass measurements of three of the planets in the Kepler-20 system that are facilitated by 104 radial velocity measurements from the HARPS-N spectrograph and 30 archival Keck/HIRES observations, as well as an updated photometric analysis of the Kepler data and an asteroseismic analysis of the host star ( = and = ). Kepler-20b is a planet in a 3.7 day period with a mass of , resulting in a mean density of , indicating a rocky composition with an iron-to-silicate ratio consistent with that of the Earth. This makes Kepler-20b the most massive planet with a rocky composition found to date. Furthermore, we report the discovery of an additional non-transiting planet with a minimum mass of and an orbital period of ∼34 days in the gap between Kepler-20f (P ∼ 11 days) and Kepler-20d (P ∼ 78 days).
Gesehen am 20.05.2020